2014
DOI: 10.1111/jfd.12243
|View full text |Cite
|
Sign up to set email alerts
|

Infections by Renibacterium salmoninarum and Nanophyetus salmincola Chapin are associated with reduced growth of juvenile Chinook salmon, Oncorhynchus tshawytscha (Walbaum), in the Northeast Pacific Ocean

Abstract: We examined 1454 juvenile Chinook salmon, Oncorhynchus tshawytscha (Walbaum), captured in nearshore waters off the coasts of Washington and Oregon (USA) from 1999 to 2004 for infection by Renibacterium salmoninarum, Nanophyetus salmincola Chapin and skin metacercariae. The prevalence and intensities for each of these infections were established for both yearling and subyearling Chinook salmon. Two metrics of salmon growth, weight residuals and plasma levels of insulin-like growth factor-1, were determined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Our results support a previous study that showed encysted N. salmincola metacercariae can increase mortality from a marine bacterial infection in juvenile Chinook Salmon (Jacobson et al 2003). Few studies have investigated co-infection effects of digenean metacercariae and bacterial infections on fish despite the common cooccurrence of these pathogens in juvenile salmonids (e.g., Sandell et al 2015) and other fishes (e.g., Xu et al 2007). Most studies involving larval digenean bacteria co-infection in fish have shown that increased mortality or bacterial invasion occurs when fish are concurrently challenged with cercariae and bacteria (e.g., Bolbophorus spp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results support a previous study that showed encysted N. salmincola metacercariae can increase mortality from a marine bacterial infection in juvenile Chinook Salmon (Jacobson et al 2003). Few studies have investigated co-infection effects of digenean metacercariae and bacterial infections on fish despite the common cooccurrence of these pathogens in juvenile salmonids (e.g., Sandell et al 2015) and other fishes (e.g., Xu et al 2007). Most studies involving larval digenean bacteria co-infection in fish have shown that increased mortality or bacterial invasion occurs when fish are concurrently challenged with cercariae and bacteria (e.g., Bolbophorus spp.…”
Section: Discussionsupporting
confidence: 91%
“…Macroparasites typically have an aggregated distribution in the wild, with few to no parasites in the majority of hosts and high parasite intensities in a small percentage of hosts (Lester 1984;Ferguson et al 2011a). For example, mean N. salmincola intensities in wild juvenile Chinook Salmon caught off the coast of Oregon and Washington ranged from 18 to 73 metacercariae, but these fish included a small proportion (∼5%) of individuals with intensities exceeding 200 metacercariae (Jacobson et al 2008;Sandell et al 2015). Thus, it is possible the effects of co-infection on mortality occur only in the heavily N. salmincola-infected proportion of the out-migrating population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into the effects of pathogens on the growth of fishes are scarce, with little research having been performed on salmonids (Speare et al ., ) or outside of the laboratory (Sandell et al ., ). For salmonids and other teleosts, body growth can be inferred from their otoliths, the calcified structures in the inner ear whose incremental depositions are proportional to changes in fish length (Campana & Neilson, ; Campana, ).…”
Section: Introductionmentioning
confidence: 99%
“…In western North America, infections are widespread among Pacific salmon in fresh water and in the ocean (Banner et al 1986, Meyers et al 1993, Kent et al 1998 and also in cultured salmon (Evelyn 1993). The bacterium has frequently been detected in juvenile Pacific salmon in fresh and coastal waters of the western USA (Sanders et al 1992, Arkoosh et al 2004, Van Gaest et al 2011, Sandell et al 2015. The mean prevalence of R. salmoninarum in juvenile Chinook salmon from 12 coastal locations ranged from 10 to 68% (Arkoosh et al 2004).…”
Section: Discussionmentioning
confidence: 99%